KEMAMPUAN GURU DALAM MENGATASI KESULITAN BELAJAR MATEMATIKA SISWA MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK DI KELAS IV MI AT-TAHZIB - Anes Rizki; Faras Sita Adilla, Rakmah , Djuita Hidayati (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to describe the ability of teachers to overcome students' difficulties in learning mathematics in elementary school through a realistic mathematical approach. The method used is qualitative descriptive with the research subject of grade IV teachers. The results showed that the difficulties experienced by grade IV students in learning at MI At-tahzib were students' low thinking ability. Internal factors of students are students' readiness to learn mathematics, lack of interest in students in mathematics lessons, laziness in learning experienced by students. Factors from outside the students come from the school environment, community environment, and social students. The teacher's ability to overcome difficulties in learning mathematics. Among them is that teachers apply realistic mathematics education PMR in the learning process of students, provide motivation and rewards to students, then there is still a need for guidance from teachers